Sporisorium scitamineum colonisation of sugarcane genotypes susceptible and resistant to smut revealed by GFP‐tagged strains. (27th July 2016) - Carvalho, G.; Quecine, M.C.; Longatto, D.P.; Peters, L.P.; Almeida, J.R.; Shyton, T.G.; Silva, M.M.L.; Crestana, G.S.; Creste, S.; Monteiro‐Vitorello, C.B.
Abstract: Sporisorium scitamineum is the causal agent of sugarcane smut disease. The fungus establishes a biotrophic interaction with sugarcane tissues, and unlike smut fungi of other monocot hosts, the primary meristem of sugarcane plants develops a whip‐like structure instead of a tumour‐like galls emerging from floral structures (tassels and ears). We examined (GFP)‐tagged S. scitamineum infecting tissues of three sugarcane genotypes with distinct responses to smut (susceptible, intermediate resistant and resistant). Mating compatible haploid cells gfp ‐expressing were obtained by Agrobacterium tumefaciens ‐mediated transformation (ATMT) using the integrative vector pFAT‐gfp. Regardless of the inoculation method (drop inoculation and hypodermal syringe inoculation), all genotypes were colonised by the fungus. GFP‐tagged strains of opposite mating reaction were able to: (a) grow in vitro as fluorescent yeast‐like cells; (b) generate infectious dikaryon; (c) penetrate sugarcane tissues; (d) colonise tissues by growing a filamentous network; and (e) form the characteristic highly branched hyphae within host cells. Fungal colonisation 160 DAI revealed an association of the fungus with vascular vessels disrupting their organisation in all three genotypes analysed. However, the resistant plants did not develop whips spanning the experiment time. The first whips emerged 76 DAI from plants of the susceptible genotype whereas for intermediate resistant plants whips were detected at 137 DAI. These whips were dissected and fluorescent sporogenesis and teliospore maturation were analysed. In vitro germination of recovered teliospores revealed after meiosis the formation of a three‐celled hyphal filament, where the fourth cell was likely maintained in the teliospore coat. These cells showed independent segregation of the gfp marker, as a result of gfp insertions in different chromosomes of each compatible haploid strain. This work presents the complete fungal life cycle of GFP‐marked S. scitamineum to study developmental stages in planta .